Jump contagion among stock market indices: Evidence from option markets - Herman Peter Boswijk; Roger J. A. Laeven; Andrei Lalu; Evgenii Vladimirov (Tinbergen Institute, 2021)
This paper explores the contagious propagation of jumps among international stock market indices by exploiting a rich panel of stock and options data. We propose a multivariate option pricing model designed to allow for, but not superimpose, time and space amplification of jumps in option markets. We develop a semi-parametric estimation procedure employing a continuum of moments conditions in GMM with implied states. We introduce a partial-information approach to reduce the computational complexity arising in the multivariate setting, derive the asymptotic properties of our estimators, and analyze their finite-sample performance. Our empirical results reveal evidence of jump contagion in option markets, both from the US to Europe and vice versa, with the US leading the UK and standing on equal footing with Germany. We illustrate the importance of capturing jump contagion for risk management, option pricing, and scenario analysis.
Keywords: C58; G01; G15; C14; C33; G13; 330; Jumps; Option markets; Crisis; Transmission; Spatio-temporal models; C-GMM